MODEL EVAKUASI BENCANA TSUNAMI KOTA PADANG - Kusdiantara, Rudy
Tsunami is a wave of trains which travels with high speed on the sea surface. This travelling wave is caused by the displacement of a large volume of water after the occurrence of an underwater earthquake or volcano eruption. The speed of tsunami decreases when it reaches the sea shore along with the increase of its amplitudes. Two large tsunamis had occurred in Indonesia with huge casualties and large damage. Indonesian Tsunami Early Warning System has been installed along the west coast of Sumatra. This early warning system will give about 10-15 minutes to evacuate people from high risk regions to the safe areas. Here in this nal project, an mathematical model for Tsunami evacuation is presented with Padang City as a study case. In the model, the safe areas are chosen from the existing high rise buildings, low risk region with relatively high altitude and (proposed to be build) ring road which are located in the radius of approximately 1 km from each gathering points. The model is formulated as an optimization problem with the total evacuation time as the objective function. The constraints consist of maximum allowable evacuation time in each route, maximum capacity of each safe area, and the number of people to be evacuated. The optimization problem is solved numerically using linear programming method with Matlab. Numerical results are shown for various evacuation scenarios for the city of Padang.